Design of Micro Robot for Minimally Invasive Surgery - Deiva Ganesh A (IAES International Journal of Robotics and Automation (IJRA), 2013)
Micro robots for medical applications need to be compatible with human body, remotely controllable, smooth in movement, less painful to the patients and capable of performing the designated functions. In this paper, state of the art in the design, fabrication and control of micro robots are presented. First the benefits of micro robots in medical applications are listed out. Second, the predominantly used micro robot designs are discussed. Third, the various fabrication process used in micro robot construction are presented. Fourth, the different approaches used for its operation and control in micro robot technology are narrated. Next based on the review we have designed a swimming micro robot driven by external magnetic fields for minimally invasive surgery. The advantage of EMA is that it can generate a wireless driving force. Then, the locomotive mechanism of the micro robot using EMA is presented. Using the EMA system setup various experiments have been conducted. Finally, the performance of the swimming micro robot is evaluated.